A72 INFLAMMATORY BOWEL DISEASE TRAINING DURING ADULT GASTROENTROLOGY FELLOWSHIP: A NATIONAL SURVEY OF CANADIAN PROGRAM DIRECTORS AND TRAINEES. (1st March 2018) - Rumman, A; Pivovarov, K; Fortinsky, K J; Nguyen, G C; Gallinger, Z
Abstract: Background: Clinical training in inflammatory bowel disease (IBD) is a major component of adult gastroenterology fellowship. As Canadian residency programs adopt a competency-by-design (CBD) training model, there is a need to identify core competencies in IBD training. Aims: This study aims to identify priorities and deficiencies in IBD clinical training among residents and program directors (PDs). Methods: Using an online and paper based platform, we administered a 15-question PD survey and 19-question trainee survey and assessed 22 proposed IBD competencies. The survey was previously developed and administered to US gastroenterology trainees and PDs. Results: Surveys were completed by 9/14 (62.3%) PDs and 44 trainees. Both trainee years were equally represented (22 residents in each year of training). All respondents were based at university teaching hospitals with full time IBD faculty on staff. All training programs surveyed offered an additional year of advanced IBD fellowship training. Dedicated IBD rotations were not offered by over half of training programs, and IBD exposure was mostly commonly encountered in inpatient rotations. Overall, only 14 (31.2%) trainees were fully satisfied with the level of IBD exposure during training. Thirty-six (81.8%) trainees reported being comfortable with inpatient IBD management, whereas only 23 (52.3%) trainees reported being comfortable with outpatient IBD management. There was a strong concordance between the proportion of PDs ranking a competency as essential and trainee comfort in that area (Pearson's rho 0.59; p=0.004). Fewer than half of trainees reported comfort in 11/22 (50%) proposed competencies. Identified areas of deficiency included phenotypic and endoscopic classification of IBD, inpatient management of severe active IBD, perianal disease management, monitoring biologic therapy, and extra-intestinal manifestations of IBD. Conclusions: Only one-third of Canadian gastroenterology trainees are fully satisfied with the level of IBD exposure under the current training model. Furthermore, several IBD core competencies appear to be inadequately covered during training. Our findings, which parallel previously published US data, highlight the need for additional focus on IBD during gastroenterology fellowship. It is possible that the optimal treatment of patients with IBD may require advanced specialists. Funding Agencies: None